2015
DOI: 10.1016/j.ijgo.2015.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus among women attending prenatal care at Korle‐Bu Teaching Hospital, Accra, Ghana

Abstract: GDM was found in 10% of pregnant women in Accra. Women who were obese by 20-24 weeks of pregnancy had a significantly increased risk of GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 22 publications
1
42
2
Order By: Relevance
“…Lower prevalence has been reported in African countries including Ghana (9.3%) [16], South African (9.1%) [21] and Nigeria (8.6%) [22] compared with developed regions like North America (12%) and Europe (14%) [2]. But Africa appears to be catching-up fast as pockets of high cases have recently been reported in Tanzania (19.5%) [23], South Africa (25.8%) [24] and Morocco (23.7%) [25].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Lower prevalence has been reported in African countries including Ghana (9.3%) [16], South African (9.1%) [21] and Nigeria (8.6%) [22] compared with developed regions like North America (12%) and Europe (14%) [2]. But Africa appears to be catching-up fast as pockets of high cases have recently been reported in Tanzania (19.5%) [23], South Africa (25.8%) [24] and Morocco (23.7%) [25].…”
Section: Discussionmentioning
confidence: 87%
“…Also, population-based prevalence from peri-urban and rural settings is unavailable. Current data on GDM in Ghana shows a prevalence of 9.3% using 2-h OGTT >8.5 mmol/l [16]. Given that this study was conducted in the largest referral/teaching hospital in Ghana where 92.5% of the study participants were urban dwellers, findings might not be representative of the typical Ghanaian population where lower population-based prevalence is hypothesized.…”
Section: Methods and Findingsmentioning
confidence: 86%
See 2 more Smart Citations
“…A recent review showed that merely 11% of countries had published prevalence data of GDM . Reported rates of GDM prevalence for Africa are in the range of 8.8%–9.3% . Within South Africa, varying rates of prevalence could be due to differences in population, screening practices, and diagnostic methods .…”
Section: Introductionmentioning
confidence: 99%